Hybrid MAC for Military UAV Networks - Kim, Gyu Seon; Lee, Hyunsoo; Park, Chanyoung; Jung, Soyi; Kim, Jae Hyun; Kim, Joongheon (International Conference on Information Networking, 2023)
Unmanned Aerial Vehicles (UAVs) are being studied extensively for military use because of their advantages of fast maneuverability and ability to penetrate deep into enemy positions. In particular, when UAVs are operated for military purposes, swarm flight and stable communication technology must be considered due to the nature of mission performance. In this paper, we propose a Hybrid MAC UAV model that can communicate at high speed even in swarm flight of multiple UAVs by varying the communication method (CSMA/TDMA) according to the movement of the UAVs on the battlefield. The sensor accepts nine sensor parameters and recognizes the external environment of the UAV. Based on this, it aims to create an "External Environment Self-Learning-based MAC (Medium Access Control)."By making a UAV with Raspberry PI and implementing it through actual flight tests, it evaluates the practical communication excellence of the Hybrid MAC UAV and suggests its applicability on the battlefield.
Keywords: Aerial vehicle; Communicationtechnology; External environments; High Speed; Hybrid Media; Manoeuvrability; Military use; Mission performance; Vehicle modelling; Vehicle network